Analisa Tax Avoidance dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Ricky Agustian; Agus Munandar (Jurnal Riset Akuntansi Politala, 2026)
This article aims to examine how tax avoidance and firm size affect firm value. This study takes quantitative methods and utilizes the automotive industry population listed on the Indonesia Stock Exchange from 2019 to 2024. The sample in this article was determined using non-probability sampling with purposive sampling techniques. The results of the article show that, overall, tax avoidance and frim size are correlated with firm value. Partially, tax avoidance is significantly positively correlated with frim value, while firm size has a significant negative impact on industry value. Future article is recommended to discuss more comprehensively the relationship between company value and other company sectors, as well as to conduct research over a longer period of time and include control variables or add more varied variables such as company growth, tax planning, or profitability.